Thermohydraulic performance evaluation of a heat exchanger mounted with oval inclined twisted rings - P. Samruaisin; V. Chuwattanakul; P. Thapmanee; M. Kumar; P. Naphon; N. Maruyama; M. Hirota; S. Eiamsa-ard (Engineering Science and Technology, an International Journal)
This research examines the effects of oval inclined twisted rings (I-TRs) on thermal performance characteristics. Heat transfer enhancement, friction factor, and thermal enhancement factor tests were conducted under uniform wall heat flux with Reynolds numbers (Re) varying from 6000 to 20,000. A systematic investigation was carried out to examine the influence of different pitch ratios (p/D) and oval-ring inclination angles (θ) on thermal enhancement factor (TEF). The experimental results reveal that the Nusselt number increases with decreasing pitch ratio (p/D) and inclination angle (θ) of the I-TRs. At p/D = 1.5, the Nusselt numbers are approximately 8.59 % to 18.78 % higher than those for I-TRs with p/D values of 2.0 and 2.5. At the smallest inclination angle, θ = 30°, the Nusselt numbers are approximately higher than those at θ = 45°, 60°, 75°, and 90° by around 1.56 %, 7.21 %, 13.74 %, and 27.14 %, respectively. At a p/D ratio of 1.5 and an inclination angle of θ = 30°, the resulting thermal enhancement factor (TEF) consistently exceeds unity across the entire Reynolds number (Re) range. In contrast, for other geometries and configurations, some TEF values fall below unity at higher Re. Within the studied range, the highest TEF of 1.12 is achieved at θ = 30°, p/D = 1.5, and Re = 6,000. The key finding suggests that the performance of the thermal system is highly dependent on both the configuration and operational conditions.